Quality aspects of oven-dried whole (full-fat) and d-oiled mealworm stored at room temperature - Khan, SZ; Usman, A; Khan, K; Ali, P; Shah, AA; Khan, H; Israr, M (Journal of the Hellenic Veterinary Medical Society, 2024)
Mealworms (Tenebrio molitor) are considered the potential novel alternative source of protein for sustainable food production and also have a low ecological footprint. Nonetheless, fresh mealworms have a shorter shelf-life, therefore, to preserve their nutrient quality and safety it is of utmost importance to optimize the post-harvest processing techniques. Therefore, in the present study, two technological forms of oven-dried (60 0Ċ for 2 h) mealworms namely whole (full-fat) mealworms (WMW) and de-oiled mealworms (D-OMW) were analysed for nutrient quality, microbial count, and aflatoxin B1 safety levels. Both WMW and D-OMW were stored for 56 days at room temperature (25 to 30 0C) and were sampled on alternate weeks (days 0, 14, 28, 42, and 56, respectively) for analysis. In comparison to WMW, the D-OMW contains high (P < 0.001) contents of crude protein (CP) and dry matter (DM). Notably, at 56 days of storage interval, the D-OMW is more stable with CP and DM contents having DM (87.3 vs. 77.3%) and CP (76 vs. 46.0%) contents. In contrast, WMW had high (P < 0.001) content of EE than D-OMW (24.5 vs. 3.30%) at 56 days of storage. Moreover, WMW and D-OMW are rich sources of minerals, particularly potassium and phosphorus, with no significant (P > 0.05) effect during storage interval. Notably, leucine, lysine, and valine are the abundant amino acids in WMW and D-OMW. During the entire storage period, no growth of Escherichia coli, Salmonella, Campylobacters, and Clostridium perfringens were found. However, low levels of other coliforms, Enterococci, and Staphylococcus aureus were detected in D-OMW than in WMW. Likewise, the aflatoxin B1 contamination level was much lower in D-OMW during the entire storage time. This study concluded that storage times affected the nutrient profile and safety level of WMW. Nonetheless, the D-OMW was found almost stable and safe even at the storage of 56 days at room temperature.